PREVALENCE OF DIABETIC RETINOPATHY IN NEWLY DIAGNOSED PEOPLE WITH TYPE 2 DIABETES IN UZBEKISTAN - Normatova, Nargiza M. (International Journal of Psychosocial Rehabilitation, 2020)
Background. Diabetes mellitus takes the third place as a cause of death, following cardiovascular and oncological diseases. The purpose of the study is to evaluate the prevalence of DR among newly diagnosed patients with type 2 diabetes by means of screening in 6 pilot regions of Uzbekistan. Materials and Methods: We screened 944 patients with newly diagnosed type 2 diabetes for DR. 62% was female, 38% were male, and the average age was 59.39±10.22 years. Screening included medical history taking, measurement of blood pressure, BMI, fasting glycaemia, HbA1c, ECG and examination by the multidisciplinary team of doctors (endocrinologist, ophthalmologist, and cardiologist). Results: the prevalence of DR among patients with newly diagnosed diabetes was 11.5% (n = 108), of which 8.7% had non-proliferative (n = 82), 2.5% - preproliferative (n = 23), and 0.3% - proliferative (n = 3) stage. DR was diagnosed mainly in patients with long-time decompensation state (HbAlc> 9%), which indicates the duration of the disease as the main factor in the progression of DR. Conclusion: The effective control of various risk factors (blood pressure, glycaemia and lipid metabolism) in prevention of vascular complications of diabetes can significantly slow down the development of microvascular lesions of the retina.